Transversus abdominis plane block with general anesthesia blunts the perioperative stress response in patients undergoing radical gastrectomy - Ruizhu Liu; Haiyan Qin; Meng Wang; Kai Li; Guoqing Zhao (BMC Anesthesiology, 2019)
Abstract Background Surgical stress induces the release of neuroendocrine mediators and cytokines during perioperative period, which may have adverse effects on cancer patients. While the surgical stress responsse can be affected by anesthetic technique. Therefore, we designed this study to assess whether subcostal transversus abdominis plane (TAP) block can affect perioperative neuroendocrine stress response, postoperative analgesia and postoperative recovery in patients undergoing radical gastrectomy under general anesthesia. Methods Sixty-five patients were recruited. Patients randomly received general anesthesia (control group), or general anesthesia combined with TAP block (40 mL of 0.375% ropivacaine) (TAP group). The primary outcome was neuroendocrine levels including norepinephrine (NE), epinephrine (E), cortisol (Cor), glucose (Glu), interleukin (IL)-6 and IL-10 during 48 h after surgery. Secondary outcomes included pain score, hemodynamic variables and recovery characteristics. Results Data from 61 of 65 patients were analyzed. The levels of NE, E, Cor, and Glu were blunt by TAP block during perioperative period. The levels of IL-6 and IL-10 were significantly lower in TAP group than in control group. TAP block efficiently relieved postoperative acute pain up to 12 h postoperatively with more stable perioperative hemodynamics compared with control group. Conclusions Subcostal TAP block blunts perioperative stress response and provides efficient analgesia, with good hemodynamic stability and minimal adverse effects.